(untitled) (Nepal Journal of Epidemiology, 2011)
Background Anxiety is the most widespread psychiatric disorder and generalized anxiety disorder is the most common disease seen in the primary care setting. Currently there are a number of anxiolytic drugs commercially available in the market for treatment of these disorders such as Benzodiazepines like Diazepam, Chlordiazepoxide, Alprazolam, Betablockers like Propranolol and H1 Antihistaminics like Hydroxyzine. Some of the newer anxiolytics like Buspirone in Azapirone group is marketed as better anxiolytic drug than the traditional drugs. Buspirone is promoted as a better drug for anxiety, as it does not cause any sedation, tolerance or physical dependence. A need for study further increases as there is no sufficient data on utilization pattern of anxiolytics on Nepalese population. This is the first study done in the utilization pattern of anxiolytic drugs in inpatient in Nepal. Methods This is an observational study undertaken between 1st October 2009 and 31st March 2010 at the Psychiatric inpatient Department of Manipal Teaching Hospital. The prescribing pattern of Anxiolytic drugs was measured. Out of a total of 240 cases who were admitted to psychiatry inpatient ward, 38 cases have received Anxiolytic drugs. Those who were critically ill with anxiety were included in the study. Results Out of 240 cases who were admitted to psychiatry inpatient, 130 were male patients (54.2%), 95% CI [47.9,60.5] and the rest were female patients (45.8%), CI [39.5,52.1] . In 38 cases of anxiety, the age of the patient <40 years 89.5% and >40 years 10.5%. Anxiety was more common in females 71.1% than in males 28.9%. 68.4% of the patients were unemployed whereas only 31.6% of the patients were employed. 78.9% of the drugs were prescribed by trade name. Among the anxiolytics, the commonest drug prescribed was Alprazolam (50%), followed by Clonazepam (31.6%), Chlordiazepoxide (15.8%) and Lorazepam (2.6%). Conclusion Utilization patterns of drugs for anxiolytics were according to treatment guidelines and suggested a trend towards the use of shorter acting Benzodiazepines such as Alprazolam. Continuous and prolonged use of longer acting Benzodiazepines has resulted in dependence and may have withdrawal symptoms when the dosage of these drugs is reduced or treatment is stopped. http://dx.doi.org/10.3126/nje.v1i4.5753 Nepal Journal of Epidemiology 2011;1(4):119-125